A study regarding availability and utilization of services of the government health facility in village Nagkalan, district Amritsar, Punjab - Bakshi, Ritika; Singh, Tejbir; Mahajan, Sanjeev; Kaur, Jasleen; Lal, Mohan; Deepti, Shyam Sunder (International Journal Of Community Medicine And Public Health, 2019)
Background: Health care expenses induced impoverishment in the poverty stricken strata of rural India is a major issue. The government of India has come up with various services in public health facilities, but there are various factors which curtail the utilization of available services and people have to visit some private health facility. The present study deals with the extent of utilization of services of government health facility and the factors impeding the utilization. Methods: The present cross sectional study was conducted in village Nagkalan, district Amritsar, where the eldest adult members present in the house at the time of the visit, and are interviewed using a semi-structured and predesigned questionnaire. A total of 1123 families were included in the final analysis. Data was compiled, analysed and valid conclusions drawn. Results: Almost all the respondents were aware about the existence of subsidiary health centre in the village. However, out of those who were aware, 40.8% never visited the centre. Utilization was more in the lower socio economic status. Immunization services followed by treatment for common ailments constituted the top two reasons for visiting the centre. Out of those visiting the centre, 80.7% were not satisfied with the current timings of the centre; only 20.2% were attended by the doctor and 33.3% reported that the prescribed medicines were never available at the centre. Conclusions: Regular supply of prescribed medicines, availability of the doctor and appropriate timings are critical for utilization of health care services at the government health facility.